A Study of the Filtration Efficiency of the N95 Medical Mask After Sterilization with the Developed Automatic Coronavirus Sterilizer - Sungthong, Apichart; Somgern, Chaiwat; Boonsee, Thitinun; Saekow, Bunpot; Porntheeraphat, Supanit (Journal of Applied Research on Science and Technology (JARST), 2022)
This research aims to develop an automatic coronavirus sterilizer. A research team which knowledge and experience in the branch of photonics technology for medical, together with a research team of virology jointly research to solve the aforementioned problems. Therefore, the system is designed as automatically sterilization process that is UV-C exposure, hot air dryer, packaging and sealing for the personal individual masks. We have found that the UV-C dose that can kill the amount of 200 microliters of coronavirus PEDV (more than the number of possible natural contamination) on N95 medical mask (model VFLEX 9105) within 1 minute and can kill the same amount of coronavirus faster than 1 minute for higher UV-C intensity. The filtering efficiency of the medical masks which were through our sterilization machine have been sent to tested. It was found that the control mask and used mask that sterilized for 10- and 30-time cycles had no significant different filtration efficiency. This demonstrates that our automated coronavirus sterilizer prototype is not destroyed the filtration efficiency of the tested medical mask so this prototype is many advantages for killing the coronavirus may be on used medical masks and can be reused many times.